Residualidad de glifosato y AMPA en huertas convencionales y agroecológicas de la provincia del Chaco - Schahovskoy, Nara Cecilia; Rojas, Julieta Mariana; Toledo, Diana Marcela; Aparicio, Virginia Carolina (Sociedad Argentina de Agroecología, 2023)
Poster